Challenges of nurses and family members of burn patients: Integrative review - Yi Wang; Frances Kam Yuet Wong; Jonathan Bayuo; Loretta Yuet Foon Chung; Li Zhang; Taotao Wang (Wiley, 2023)
Abstract Aims To identify the challenges facing burn care nurses and burn patients' family members and to explore the relationship between the above challenges. Design Whittemore and Knafl's integrative review. Methods Databases used for this review included Cochrane Library, Web of Science, PubMed and Embase. The original research published from January 2010 to November 2021 was selected. Studies reporting the challenges of family members or nurses of burn patients identified through extensive database search were considered for inclusion. The Mixed‐Method Appraisal‐Tool was applied for the evaluation of the quality of the literature. The analysis approach used was content analysis. Results Of the 2746 identified studies, 17 studies were included. Key findings related to the challenges facing nurses and family members of burn patients were extracted. The themes relating to burn care nurses included ethical and religious issues, clinical issues, work-life imbalance and limited support. The themes relating to family members included family's different views on prognosis and treatment, work-life imbalance, psychological issues and lack of multifaceted support. The challenges for the formal and informal caregivers are similar and there is existence of some shared concerns. If the above challenges are not resolved, support for the burn patients may be adversely affected. Corresponding measures should be taken to overcome such challenges.